تقييم إمكانيات دمج نمذجة معلومات البناء )BIM)، إنترنت األشياء )IoT)، والذكاء االصطناعي )AI )مع نظام التوصيل المتكامل )IPD )لتعزيز االلتزام بالجداول الزمنية في قطاع البناء الليبي (Comprehensive Journal of Science, 2025)
The Libyan construction sector faces chronic challenges, includingschedule delays, cost overruns, and inefficiencies stemming from political instability andlimited technology adoption. This study assesses the potential of integrating BuildingInformation Modeling (BIM), Internet of Things (IoT), and Artificial Intelligence (AI) withIntegrated Project Delivery (IPD) to enhance schedule compliance. Employing a quantitativeapproach, a structured survey was distributed to 150 construction professionals in Libya,yielding 120 valid responses (80% response rate). Data analysis was conducted usingSPSS, incorporating descriptive statistics and multiple linear regression. Results indicatehigh familiarity with BIM (67.5% familiar or very familiar), but lower for AI (47.5% unfamiliaror slightly familiar) and IPD (40.8%). Perceived impact on schedule compliance waspositive, with BIM rated highest (77.5% high or very high impact). Key barriers include highimplementation costs (92.5%) and skill shortages (84.1%). Regression analysis revealed asignificant negative relationship between knowledge level and perceived impact (β = -0.374,p < 0.001), suggesting that more knowledgeable professionals adopt a more realistic view ofcontextual challenges. The study recommends training programs, government incentives,and phased adoption to foster digital transformation, contributing to the sector's recovery inLibya.
Keywords: word; word; word; (not more than 7 words)